Dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) in the El Zapotal reserve, Chiapas, Mexico - Rodríguez-López, M. Edivaldo (2019)
El Zapotal Recreational Ecological Preserve (CEREZ) is characterized by presenting one of the last remnants of tropical forest in the central region of Chiapas, Mexico. However, the knowledge of some taxa of the reserve is not entirely adequate. In this work the composition and structure, as well as the temporal distribution of the dung beetles that reside in CEREZ, are analyzed. Monthly samplings were carried out between February 2013 and January 2014 using pitfall traps baited with dung of six mammal species that are kept in captivity inside the Miguel Álvarez del Toro Zoo (ZooMAT). An annotated checklist of 22 species grouped into 12 genera and six tribes of Scarabaeinae is presented. Onthophagus anthracinus, Canthon femoralis, Onthophagus landolti, and Copris laeviceps provide 89.7% of the total abundance. The rarefaction curve shows an asymptotic tendency, with 92% completeness. The captured fauna showed a marked temporal distribution (p < 0.01), observing the highest values of richness and abundance during the months of the rainy season. The records represent 7.53% of the species diversity known in Mexico and 18.2% of the reported in the Chiapas state. Despite representing a small remnant of tropical forest and the constant anthropic pressure generated by the urban area, El Zapotal conserves a representative fauna of dung beetles at the regional level, Highlighting the importance of the reserve as a refuge for species.